Conversion disorder in children and adolescents: clinical features and comorbidity with depressive and anxiety disorders - Pehlivantürk, Berna; Ünal, Fatih (The Turkish Journal of Pediatrics, 2000)
The aim of this study was to determine some of the demographical and clinical characteristics of conversion disorder in children and adolescents and to ascertain comorbidity with depressive and anxiety disorders. For this purpose 51 children and adolescents (mean age: 13.2 ± 1.9 , range: 9-16 years) who met DSM-IV criteria for conversion disorder were compared with a control group. The subjects of this study were mostly postpubertal girls, and pseudoseizure was the most frequent presentation. Misdiagnoses were frequent among these patients. Eight (15.7%) patients received a comorbid diagnosis of major depression and 19 (37.2%) patients had comorbid anxiety disorders according to DSM-IV diagnostic criteria. Significant differences between the two groups on depression and anxiety scales supported the clinical findings. It was concluded that clinicians should screen every patient with conversion disorder for major depression and anxiety disorders for a better outcome.
Keywords: conversion disorder; children; adolescents; depression; anxiety